Computer-based Simulation and its Effects on Student’s Knowledge and Interest in Chemistry - Asedillas, Jhenly I.; Quimbo, Maria Ana T. (International Journal on Open and Distance e-Learning, 2019)
Central to learning Chemistry is the development of fluency across various representations such as symbolic-, macroscopic-, and particulate-levels. “Simulations that support multi-representational fluency are considered critical (Moore, Chamberlain, Parson, & Perkins, 2014)” because of the inherent difficulty of Chemistry as a subject matter. This action research, aimed at analyzing the effects of computer simulation on students’ knowledge and interest in Chemistry, used a quasi-experimental research design. The participants of the study were three intact classes from different learning groups in a male boarding school in Southern Tagalog province. Four Physics Education Technology (PhET) interactive simulations were used in teaching the concepts of chemical reaction for three weeks. Pre- and post-test scores of the students showed that there is an increase in students’ knowledge and is highest in the advance group. The result of the interest survey showed that advance and proficient students were highly interested while students approaching proficiency were moderately interested in learning Chemistry using simulation. Students revealed that they enjoyed using the computer-based simulation while learning Chemistry because (1) of the stars that they virtually receive and the challenges posed in the game levels, (2) the material is easy to manipulate, (3) they perform the activity with minimal supervision, thus making them feel independent, and (4) the material contains practice exercises and a game after the topic introduction. The computer-based simulation is recommended to be employed in classroom instruction to increase students’ knowledge and interest in Chemistry.